Agronomic behavior of cowpea varieties in non-alluvial soils of the Peruvian Amazon - Angulo Villacorta, Carlos Darwin (2022)
Grain legumes in tropical areas are of great importance as a food source, especially in rural communities. Little is known about their adaptability and behavior in non-alluvial soils of the Peruvian Amazon. Our objective was to assess the agronomic behavior of cowpea varieties in non-alluvial soils. The experiment was performed in completely randomized design with four treatments and four repetitions. Each experimental unit consisted of five rows of 6m length by 0.5m between plants and 1m between rows. The variables evaluated were: plant height (cm), number of pods, pod length (cm), number of graind per pod, grain length (mm), grain width (mm), and weight of 100 seeds (g). An analysis of variance and Tukey’ test at 5% probability were used to determine significant differences between treatments. Results showed significant differences between varieties according to the evaluated variables. The red cowpea presented significant differrences for the agronomic characteristics in plant height (62.83cm), grain length (8.68mm), and weight of 100 seeds (16.87g) in relation to the other varieties. The Chiclayo Olho Preto variety stood out only in grain width (5.46mm), and the Chiclayo Vermelho in pod length (19.58cm). The red cowpea has the potential to be cultivated preliminarily in larger-scale areas in the Yurimaguas district